Different kinds of documentary credit: remarks for export-import enterprises and commercial banks in Vietnam,Bachelor's thesis - Dang Thanh Trung,Nguyen Thi Hong Hai
Different kinds of documentary credit: remarks for export-import enterprises and commercial banks in Vietnam : Bachelor's thesis / Dang Thanh Trung; Nguyen Thi Hong Hai supervisors .- H. : Banking Academy , 2019 .- 69 p. ; 29 cm